Divergent tracks how three film communities revolutionized digital film sound - Ament, Vanessa Theme 1955- (Bloomsbury Academic, 2021)
"By examining three case studies of award-winning soundtracks from cult films-Barton Fink (1991), Bram Stoker's Dracula (1992), and The English Patient (1996)-it becomes clear that major American film communities, when confronted with the initial technological changes of the 1990s, experienced similar challenges with the inelegant transition from analogue to digital. However, their cultural and structural labor differences governed different results. Vanessa Ament, author of The Foley Grail (2009), rather than defining the 1990s as an era of technological determinism-a superficial reading-it is best understood as one in which sound professionals became more viable as artists, collaborated in sound design authorship, and influenced this digital transition to better accommodate their needs and desires in their work"--